Fuzzy interval optimal control problem - Campos, José Renato [UNESP]; Assunção, Edvaldo [UNESP]; Silva, Geraldo Nunes [UNESP]; Lodwick, Weldon Alexander; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Maqui-Huamán, Gino Gustavo [UNESP] (Elsevier, 2019)
This paper proposes the discrete-time fuzzy interval optimal control problem via single-level constrained fuzzy arithmetic. Fuzzy interval functions are established and allow us to evaluate the dynamics of the fuzzy interval difference equation. Moreover, fuzzy interval dynamic programming is developed to obtain the optimal fuzzy interval solution helping us to make a realistic decision. A numerical example illustrates the theory and provides the practical solution for an user.
Keywords: Fuzzy interval difference equation; Fuzzy interval dynamic programming; Fuzzy interval optimal control problem; Single-level constrained fuzzy arithmetic